2022
DOI: 10.1017/dap.2022.16
|View full text |Cite
|
Sign up to set email alerts
|

The changing roles of frontline bureaucrats in the digital welfare state: The case of a data dashboard in Rotterdam’s Work and Income department

Abstract: The welfare state is currently undergoing a transition toward data-driven policies, management, and execution. This has important repercussions for frontline bureaucrats in such a “digital welfare state.” So far, impact of data-driven tools on frontline bureaucrats is primarily described in terms of curtailing or enlarging their discretionary space to make decisions. It is unclear, however, how daily work practices and role identities of frontline bureaucrats change in situ and which norms they develop to work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Several authors suggested that in order to understand value creation, the making of norms, ethics, and accountability must be understood in practice. Contributions approached these topics focusing on different units of analysis, including the moral improvisation work of frontline workers who must develop new roles in interaction with a dashboard (Kersing et al, 2022), the practical activities of public institutions and media to reconstruct the origins and effects of algorithmic harms (Wieringa, 2023), a method for developing reflexive practices for data scientists (Lähteenoja and Karhu, 2023), or public-private collaborations that use citizen-generated data to address public issues (Thuermer et al, 2024). For instance, Thuermer et al highlight a lack of institutional rules, such as professional norms or funding requirements, that would align data practices with the actual needs of citizens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors suggested that in order to understand value creation, the making of norms, ethics, and accountability must be understood in practice. Contributions approached these topics focusing on different units of analysis, including the moral improvisation work of frontline workers who must develop new roles in interaction with a dashboard (Kersing et al, 2022), the practical activities of public institutions and media to reconstruct the origins and effects of algorithmic harms (Wieringa, 2023), a method for developing reflexive practices for data scientists (Lähteenoja and Karhu, 2023), or public-private collaborations that use citizen-generated data to address public issues (Thuermer et al, 2024). For instance, Thuermer et al highlight a lack of institutional rules, such as professional norms or funding requirements, that would align data practices with the actual needs of citizens.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, several of our contributions thematized the (lack of) sustainability of data infrastructures. The studies suggest that this may be related to a lack of investments to sustain the practices of staff to work with data infrastructure (Gangneux and Joss, 2022), but it is also reflected in a lack of investments in norms and the adoption of technologies (Kersing et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Data are used in an increasing number of policy domains. For example, in the domain of public security, police officers use data to deploy resources efficiently (Brayne, 2017; Meijer et al, 2021); in the social domain, civil servants use data-driven dashboards for service provisions to unemployed citizens (Kersing et al, 2022); and in the financial domain, tax professionals use data to detect frauds and social security infringements (Simonofski et al, 2022).…”
Section: Introductionmentioning
confidence: 99%